A comparative study of the survival, growth and gonad development of the diploid and triploid Hong Kong oyster, Crassostrea hongkongensis (Lam & Morton 2003). (29th April 2016) - Zhang, Yuehuan; Li, Jun; Qin, Yanping; Zhou, Yangen; Zhang, Yang; Yu, Ziniu
Abstract: The Hong Kong oyster, Crassostrea hongkongensis is an economically important and widely cultivated oyster species in southern China. Aiming to improve the aquaculture potentials of C. hongkongensis, a triploid organism was generated by inhibiting the second polar body formation in the fertilized eggs, using 0.5 mg L −1 cytochalasin B. Triploids exhibited significantly higher growth and were larger than the diploids throughout the life cycle. Much of the triploid growth advantage can be attributed to resource reallocation to structural development due to gonadal sterility. Most of the triploid oysters exhibited polymorphic sterility with atrophic gonads and abnormal gametogenesis. Only few 'dysfunctional' sperms were produced by the triploid males, thus ruling out reproductive and genetic contamination of natural oyster populations from triploid cultivations. This advantage in addition to the superior growth of triploids makes it a potent alternative in Hong Kong oyster aquaculture industry. Triploid survival was mostly found to be similar to that of diploids except for day 360, when a significant triploid advantage in terms of survival was noted. Furthermore, we found that growth and survival of Hong Kong oyster is significantly higher at the Zhuhai site in comparison to the Beihai site. Our results indicate a strong environmental effect in Hong Kong oyster cultivation and points to the fact that Zhuhai site was more suitable for oyster farming than the Beihai site. Overall, this study provides valuable information to the aquaculture industry of southern China.